TURKISH SOCIETY’S ATTITUDE TO VIOLENCE AGAINST WOMEN - ZIVDIR, Pelin; ATEŞEYAN, Yasemin; ÖZCANARSLAN, Neslihan (Göbeklitepe Medical Science Journal, 2022)
The aim of this research is to determine the attitudes of women and men towards violence against women. This cross-sectional study was carried out on 15 May-30 September 2021 with the participation of 454 people aged between 19-60 who could read and write, use a smart phone, had no visual impairment and agreed to participate in the study. The data were collected using the Descriptive Characteristics Information Form prepared by the researchers and the Attitude Scale towards Violence Against Women prepared by Gömbül (1998). The data obtained in the research were analyzed in the SPSS 25.0 statistical package program. It was determined that 37.4% of the participants were between the ages of 18-25, 78% were women, 51.8% were undergraduates, 53.1% were single, and 58.6% were working. In the study, the total score average of the scale was found to be significantly higher for those who consider arranged marriage more appropriate, those who think that one can commit violence unintentionally out of anger, and those who see violence as partly a means of discipline and acceptance (p<0.05). The attitudes of the participants towards violence against women were found below the average. However, the effect of traditionalist perspective is observed in the results of the study.